Supraphysiological Role of Melatonin Over Vascular Dysfunction of Pregnancy, a New Therapeutic Agent? - Valenzuela-Melgarejo, Francisco J.; Lagunas, Constanza; Carmona-Pastén, Fabiola; Jara-Medina, Kevins; Delgado, Gustavo (Frontiers in Physiology, 2021)
Hypertension can be induced by the disruption of factors in blood pressure regulation. This includes several systems such as Neurohumoral, Renin-angiotensin-aldosterone, the Circadian clock, and melatonin production, which can induce elevation and non-dipping blood pressure. Melatonin has a supraphysiological role as a chronobiotic agent and modulates vascular system processes via pro/antiangiogenic factors, inflammation, the immune system, and oxidative stress regulation. An elevation of melatonin production is observed during pregnancy, modulating the placenta and fetus’s physiological functions. Their impairment production can induce temporal desynchronization of cell proliferation, differentiation, or invasion from trophoblast cells results in vascular insufficiencies, elevating the risk of poor fetal/placental development. Several genes are associated with vascular disease and hypertension during pregnancy via impaired inflammatory response, hypoxia, and oxidative stress, such as cytokines/chemokines IL-1β, IL-6, IL-8, and impairment expression in endothelial cells/VSMCs of HIF1α and eNOS genes. Pathological placentas showed differentially expressed genes (DEG), including vascular genes as CITED2, VEGF, PL-II, PIGF, sFLT-1, and sENG, oncogene JUNB, scaffolding protein CUL7, GPER1, and the pathways of SIRT/AMPK and MAPK/ERK. Additionally, we observed modification of subunits of NADPH oxidase and extracellular matrix elements, i.e., Glypican and Heparanase and KCa channel. Mothers with a low level of melatonin showed low production of proangiogenic factor VEGF, increasing the risk of preeclampsia, premature birth, and abortion. In contrast, melatonin supplementation can reduce systolic pressure, prevent oxidative stress, induce the activation of the antioxidants system, and lessen proteinuria and serum level of sFlt-1. Moreover, melatonin can repair the endothelial damage from preeclampsia at the placenta level, increasing PIGF, Nrf-2, HO-1 production and reducing critical markers of vascular injury during the pregnancy. Melatonin also restores the umbilical and uterine blood flow after oxidative stress and inhibits vascular inflammation and VCAM-1, Activin-A, and sEng production. The beneficial effects of melatonin over pathological pregnancies can be partially observed in normal pregnancies, suggesting the dual role of/over placental physiology could contribute to protection and have therapeutic applications in vascular pathologies of pregnancies in the future.